Modern learning and teaching Strategies - Natia Chaganava (Foundations and Trends in Modern Learning, 2023)
The education sector has consistently evolved and transformed over the decades to adapt to modern-day developments. The latest teaching methods, with modern learning and teaching strategies, must be both knowledge- and technology-driven. This is important to thrive and progress in society as a whole. Even in the 17th century, Jan Amos Komensky considered the first and last goal was to find out such methods that would help students to study with teacher’s less interference. And with the help of this method, schools and institutions would not be boring as it was earlier. To achieve this, Comenius required a change in didactic thinking, which meant that only the teaching content should not have been the key for teachers, but also to find out and discover those methods and ways that would simplify the learning process and easy to understand. More than three centuries have passed since Comenius expressed this didactic principle. During this time, many teaching methods were developed, tested and put into practice. The effectiveness of these methods depends on how adequately we choose them. Constructivism is a philosophy of learning that explains how people come to understand or know. In the late 1980s and early 1990s, many psychologists began to turn their attention to the constructivist view of learning, which assumes that learning is an active process in which learners internally construct knowledge from interactions with their physical and social environments. Constructivists believe that many of the things we know are influenced by context and prior experiences. Conceptual growth, from a constructivist perspective, results from sharing multiple perspectives and refining our interpretations in response to other perspectives. Constructivists focus on engaging learners in richly textured contexts that are reflective of the natural environment. In such an environment, learners have opportunities to negotiate meanings and collaborate with each other.